Return On Assets Of Plantation Companies Listed On The Indonesian Stock Exchange - Gurning, Dedy; Siallagan, Hamonangan; Silalahi, Amlys (SEAN Institute, 2024)
Profitability is the company's goal and shows the ability achieved in a certain period by the company. The company's ability to earn profits is one of the clues about the quality of management and operations of the company, which means it reflects the value of the company, where with profits the company can expand its business. There are several factors that influence it, including the influence of cash turnover, accounts receivable circulation and inventory turnover. This study aims to determine and analyse its effect on profitability. The object of this research is 18 plantation companies listed on the Indonesia Stock Exchange in 2018-2021. Analysis with Evies 12 and 72 observations. The results showed that the panel data linear regression method chosen in this study was the Random Effect Model (REM). The independent variables, namely Cash Turnover, Inventory Turnover, Capital Structure (DER) partially have a negative and significant effect on Profitability, while Receivables Turnover partially has a positive and significant effect on the Profitability of plantation companies listed on the Indonesia Stock Exchange in 2018-2021 which is proxied by Return on Asset (ROA).